Survival and prognostic factors of lymphadenectomy in endometrial cancer: a Tunisian single center experience - Safta, Ines Ben; Jaidane, Olfa; Mansouri, Houyem; Doghri, Raoudha; Gadria, Selma; Mrad, Karima; Hassouna, Jamel Ben; Rahal, Khaled (International Surgery Journal, 2018)
Background: Endometrial cancer (EC) is the most common pelvic gynecological cancer. The purpose of the present study is to identify histoprognostic risk factors for lymph node involvement, evaluate the impact of lymphadenectomy on relapse and overall survival and assess prognostic factors influencing the survival rates in endometrial cancer. Methods: This was a retrospective study of 249 cases of endometrial cancer, over a period of 16 years (2000-2015). We analyzed the clinical, pathological features and outcome of our patients. Curves of overall and recurrence-free survival were performed. Results: In our cohort, stage IA was found in 46.6% of cases, stage IB in 14.5%, stage II in 13.7%, stage IIIA in 3.6%, stage IIIB in 2%, stage IIIC1 in 8.8%, stage IIIC2 in 4.4% and stage IV in 6.4%. The histologic type (p=0.02, OR=2.702, CI [1.169; 6.25]), myometrial invasion (p<0.001, OR=4.524, CI [1.960; 10.416]), lymphovascular space invasion (p=0.047, OR=2.267; CI [1.013; 5.076]) were the only independent factors of lymph node invasion in multivariate analysis. 5-years overall and recurrence free survival was 76.3% and 81.5%, respectively. Overall survival at 5 years was 64.6% with a lymph node ratio of less than 10%, 22.2% with a lymph node ratio between 10 and 50%, and zero with a lymph node ration greater than 50% (p=0.016). By studying the number of lymph nodes removed during lymphadenectomy, survival trend to be improved when the lymph node count increased. Conclusions: The lymphadenectomy has an incontestable diagnostic and prognostic value. Present retrospective study showed the therapeutic interest of lymph node dissection in endometrial cancers.